1992
DOI: 10.1007/bf00133706
|View full text |Cite
|
Sign up to set email alerts
|

Genomic distribution of transposable elements among individuals of an inbred Drosophila line

Abstract: The stability of the elements of eleven transposon families (412, B 104, blood, 297, 1731, G, copia, mdg 4, hobo, jockey and I) has been compared by the Southern technique among individuals of a Drosophila line that has been subjected to 30 generations of sister sib matings. The 412, B104, blood, 297, 1731 and G elements appear stable. Heterochromatic copia and hobo elements and euchromatic I elements appear highly polymorphic. In addition, copia, mdg 4, jockey and I elements undergo an instability resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The parameter fi estimated from such frequency data approximates 4N e u, and large differences in estimated values of fi therefore imply real variation in transposition rates of different elements. Direct observations of copia (Lim et al 1983;Eggleston, Johnson-Schlitz & Engels, 1988;Di Franco, Galuppi & Junakovic, 1992) and roo (Eggleston, Johnson-Schlitz & Engels, 1988) transpositions have been reported previously, suggesting these elements in particular transpose relatively frequently. However, we observed no 297 transpositions, but Eggleston, Johnson-Schlitz & Engels (1988) reported a trans-position rate of this element on the X chromosome alone of 2-1 x 10~4, further suggesting there is variation among strains for factors affecting transposition rate.…”
Section: (I) Variable Rates Of Transposition and Excision Among Elemementioning
confidence: 76%
“…The parameter fi estimated from such frequency data approximates 4N e u, and large differences in estimated values of fi therefore imply real variation in transposition rates of different elements. Direct observations of copia (Lim et al 1983;Eggleston, Johnson-Schlitz & Engels, 1988;Di Franco, Galuppi & Junakovic, 1992) and roo (Eggleston, Johnson-Schlitz & Engels, 1988) transpositions have been reported previously, suggesting these elements in particular transpose relatively frequently. However, we observed no 297 transpositions, but Eggleston, Johnson-Schlitz & Engels (1988) reported a trans-position rate of this element on the X chromosome alone of 2-1 x 10~4, further suggesting there is variation among strains for factors affecting transposition rate.…”
Section: (I) Variable Rates Of Transposition and Excision Among Elemementioning
confidence: 76%
“…The existence of a transposon-based mechanism to generate variability is also suggested from old and recent observations in Drosophila , showing that inbreeding generates both morphological variability (see Lerner 1954 for discussion) and transposon activation (Di Franco et al 1992; Ratner and Vasilyeva 1996). It is well known that the deterioration of populations subjected to inbreeding is a general phenomenon.…”
Section: Environmental Stress and Transposon Activitymentioning
confidence: 83%
“…Many researchers have also observed that inbreeding depression can lead to an increase in phenotypic variability that has been assumed to be of environmental origin. Relevant to this argument, inbreeding has been shown to cause transposon mobilization in Drosophila , again suggesting their involvement in generating phenotypic variability (Di Franco et al 1992). Taken together, these observations suggest that inbreeding is perceived as a stress, triggering the activation of transposons.…”
Section: Environmental Stress and Transposon Activitymentioning
confidence: 98%
“…Fixation of different host alleles in laboratory isogenic derivatives might be responsible for the transposition rate variation uncovered between laboratory lines of D. melanogaster (Nuzhdin, 1999). To take an example of one TE family, many laboratory stocks are known to have actively transposing LTR‐containing retrotransposable element copia (Biemont et al ., 1987; Di Franco et al ., 1992; Pasyukova & Nuzhdin, 1993; Charlesworth et al , 1994; Nuzhdin & Mackay, 1994). While we cannot exclude the possibility that these stocks have accumulated new mutations affecting copia transposition rate before copia instability was found, it is more likely that permissive/restrictive alleles segregate in nature.…”
Section: Introductionmentioning
confidence: 99%